Fotojornalismo: narrativa visual da pandemia de coronavírus - Venturin, Vitor Jubini (2022)
In view of the journalistic coverage of the covid-19 pandemic, we developed this work in order to investigate how the coronavirus pandemic was represented by photojournalism published on news sites in its first year in Brazil. For this, we built a research corpus with 202 images and mapped, identified the thematic patterns, selected and analyzed these photographs about the pandemic. Through a combination of two research methods, Content Analysis proposed by Bardin (2011), and Image Analysis proposed by Gervereau (2007), we reach the conclusion that part of the analysis allows us to identify thematic landmarks such as the issue of control of bodies and of space, the dark dimension of the tragedy, the politicization of the pandemic and the trust in science, expressed in efforts for a cure. We found that photojournalism is a visual narrative that collaborates with textual information as well as providing other perspectives that point to major political, social, economic and psychological impacts provided by a crisis at different levels.